Case for diagnosis. Subcutaneous nodules in the plantar region, - Diego Henrique Morais Silva; Isaura Azevedo Fasciani; Neusa Yuriko Sakai Valente; Bethânia Cabral Cavalli Swiczar (Sociedade Brasileira de Dermatologia, 2020)
Abstract The authors report a case of mobile and painful nodules on the bilateral plantar surface of a female patient referred by the rheumatology service, where she was being followed-up for rheumatoid arthritis. A nodule excision was performed for differential diagnosis and symptom relief; the histopathological analysis was compatible with a rheumatoid nodule. Although rheumatoid nodules are a common manifestation of rheumatoid arthritis, exclusive plantar involvement is seldom described in the literature.